Behaviorism language acquisition theory: a case study in the teaching And learning of Malay Language among year 1 pupils - Nazir, Faridah; , (Academic Research Publishing Group, 2018)
This paper is about Behaviorism Theory which sees human behavior as a reaction to the stimulus (stimulus to response). This theory also emphasizes the importance of rewards or incentives to stimulate and influence what and how pupils do things, including how they learn. Therefore, this study focuses on the acquisition of language during the teaching and learning of Malay Language among year 1 pupils in a primary school in Seremban, Negeri Sembilan, Malaysia. Teachers have applied this theory to train the pupils repeatedly using drill method. For example, when the teacher teaches the skills mentioned in the Malay Language syllables i.e. KV + KVK spelling pattern, the teacher will ask the pupils to repeat the pronunciation of the word a few times so that they can pronounce it properly. In this situation, learning depends on the pupils mastery of the mentioned syllables and the teacher will continue teaching the word built by the syllables which are taught earlier. Next, the pupils are asked to give examples of words constructed according to the KV + KVK pattern of syllables and the process are repeated until the skill is mastered well. Through participating observation method conducted in this study, it is found that the acquisition and mastery of a language is a learning process that needs to be practised repeatedly. Thus, the process of language teaching can be done in a more systematic way and will also improve the pupils memory. Thus, the findings also shows that, the acquisition of language using Behaviorism Theory encourages pupils to learn a language with continuous reward and reinforcement and the teachers do not have to take too long to explain the learning topics.